2003
DOI: 10.1097/01.ju.0000083883.16836.91
|View full text |Cite
|
Sign up to set email alerts
|

How to Investigate Neurovesical Dysfunction in Children With Anorectal Malformations

Abstract: Because tethered cord occurs in children without sacral anomalies as well as in those with low ARM, we recommend evaluation of all patients using MRI. When MRI is positive UDS should be performed. We agree with a previous suggestion to evaluate all males with rectourethral fistula and females with cloaca malformations. Finally we recommend a noninvasive evaluation for all other children and UDS when neurogenic dysfunction is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
2
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 16 publications
1
30
2
10
Order By: Relevance
“…Conflicting reports exist when using these radiographic characteristics to predict lower urinary tract dysfunction in ARM (21)(22)(23)(24). In our select series of males with epididymitis we did not see an association between the existence of neurogenic bladder and either sacral or spinal cord radiographic abnormality.…”
Section: Discussioncontrasting
confidence: 62%
“…Conflicting reports exist when using these radiographic characteristics to predict lower urinary tract dysfunction in ARM (21)(22)(23)(24). In our select series of males with epididymitis we did not see an association between the existence of neurogenic bladder and either sacral or spinal cord radiographic abnormality.…”
Section: Discussioncontrasting
confidence: 62%
“…11 Neurovesical dysfunction is primarily related to tethered cord or to an iatrogenic nerve injury. 16 Once symptoms appear, they are often irreversible despite surgical intervention and may have a significant impact on the continence of patients with imperforate anus. Surgical release of a tethered cord before the onset of neurological problems may prevent the onset of these symptoms.…”
mentioning
confidence: 99%
“…However, Golonka et al 23 reported that a tethered cord in children with a low lesion is as common as in those with a high lesion. Mosiello et al 16 reported that the incidence of spinal cord anomalies is 60% in those with a low lesion and 66% in those with a high lesion. In the present study, spinal cord anomalies were identified in 30% (15 of 50 patients) and vertebral column anomalies in 40% (20 of 50 patients).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Occult spinal dysraphism was suspected when the spinal cord resided below the level of the second lumbar vertebra on spinal ultrasound, if the filum terminale was diffusely thickened or if the cord appeared to be fixed to a spinal lipoma. 7 Early in our series, 4 patients underwent a 2-stage procedure in which the rectal component was repaired first, leaving the urogenital sinus for a secondary operation. In the remaining 8 girls, a 1-stage abdomino-perineal pull-through was performed.…”
Section: Resultsmentioning
confidence: 99%